Intraretinal fibrosis in exudative diabetic macular edema after ranibizumab treatments - Voraporn Chaikitmongkol (2018)
Copyright © 2014 by Ophthalmic Communications Society, Inc. Purpose: To describe the clinical and optical coherence tomography findings of an eye with diabetic macular edema that developed intraretinal fibrosis in an area previously occupied by lipid accumulating after the intravitreous ranibizumab treatment. Methods: Interventional case report. Results: An 85-year-old man presented with diabetic macular edema involving the center of the macula with a half disk area of lipid inferotemporal to the macula. He received ranibizumab treatments after the principles of the Diabetic Retinopathy Clinical Research Network retreatment guidelines. After 12 doses of intravitreous ranibizumab injections over 20 months, macular edema resolved, visual acuity improved from 20/63 to 20/40, and the central subfield thickness decreased from 404 mm to 234 mm. As the edema resolved, the area of lipid did not expand toward the fovea but was replaced by fibrosis occupying the area of lipid, only smaller in extent. Optical coherence tomography scans showed an intraretinal, dome-shaped hyperreflective area corresponding to the fibrosis. Conclusion: This case report, to our knowledge, provides the first documentation of intraretinal fibrosis replacing an area of lipid associated with diabetic macular edema after anti-vascular endothelial growth factor therapy, as had been described previously following laser photocoagulation for diabetic macular edema. Unlike some previous reports of lipid accumulating within the fovea with subsequent fibrosis corresponding to the metaplastic retinal pigment epithelium on histopathology, with or without laser treatment, the lipid in this case did not expand into the fovea before the development of fibrosis, and optical coherence tomography confirmed that the fibrosis was located in the intraretinal rather than the subretinal pigment epithelium space.